Lipids: plant biology’s slippery superheroes - Moreau, Hortense; Bayer, Emmanuelle M. (Frontiers in Plant Physiology, 2023)
Lipids are not only structural elements that make up biological membranes, they also play a crucial role in functionalising these membranes. Through their ability to modulate membrane physical properties, to act as sensors and signalling molecules, and to interact with proteins to influence their subcellular localisation and activity, lipids contribute the intricate workings of plant cells. The enrichment of specific lipids within distinct subcellular compartments aids to the establishment of membranes unique identity and properties. Lipids are major regulators of many cellular processes including cell signalling, cell division, cell polarity, membrane trafficking, intra-and intercellular communication, cell growth, and responses to environmental stress. In fact, the immense diversity of lipid species provides plant cells with an extensive arsenal of tools to establish distinctive biochemical identities within their membranes. In this review, we present an overview of plant membrane lipids, emphasizing their role in environmental stress response by highlighting recent advancements in the field.ne